Management and outcomes of non–small cell lung cancer patients with rapid progression under second‐or‐more‐line immune checkpoint inhibitors: ERORECI study (GFPC 2016‐04). (20th November 2019) - Vergnenegre, Alain; Geier, Margaux; Guisier, Florian; Lamy, Regine; Comet, Bénédicte; Le Garff, Gwenaelle; Do, Pascal; Janicot, Henri; Morel, Hugues; Decroisette, Chantal; Andre, Michel; Falchero, Lionel; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) have been approved as second‐line therapy for advanced non–small cell lung cancers (NSCLCs) progressing after platinum‐based chemotherapy. However, some patients' disease progressed rapidly and sometimes exhibited explosive tumor progression. This descriptive, prospective study aimed to assess the characteristics of nonresponders with rapid progression (RP), defined as progression‐free survival (PFS) ≤2 or 2‐4 months under ICIs. Methods: This analysis included all consecutive ICI‐treated (second‐or‐more line) patients with RP ≤4 months from 1 September 2016 to 31 August 2017 and compared the clinical characteristics, treatments, and outcomes (overall survival [OS]; responses; PFS, according to treatment line) of NSCLCs that progressed after ≤2 vs 2‐4 months on ICIs. Results: Comparisons of the 224 (70.2%) patients with ≤2‐month and 95 (29.8%) with 2‐ to 4‐month RP revealed the former had less frequent nonsmokers and ECOG PS = 0, more frequent stage IV disease and higher neutrophil/lymphocyte ratio. Their respective ICI PFS rates were: 1.6 [95% CI: 0.1‐2] and 2.7 [2.0‐4.2] months, with 16.5% and 11.6% having partial responses to first‐ and second‐line therapies post‐ICI chemotherapy. Their respective median OS rates were 6.0 and 9.0 months ( P  ≤ .009). Multivariate analysis retained only PFS of the first‐line therapy pre‐ICI and neutrophil/lymphocyte ratio at ICI onset as being significantly associated with ≤2‐month RP. Conclusion: In the real‐life setting, NSCLC RP on ICI remains a challenge. New descriptive and analytic studies are needed to identify factors predictive of RP. Abstract : Immune checkpoint inhibitors (ICIs) have been approved as second‐line therapy for advanced non–small cell lung cancers (NSCLCs) progressing after platinum‐based chemotherapy. However, some patients' disease progressed before 2 or 4 months—without any response—and sometimes exhibited explosive tumoral progression. This descriptive prospective study aimed to assess the management and clinical outcomes of nonresponders with rapid progression, defined as progression‐free survival ≤2 or 2‐4 months under ICI.